Aqueous porous phosphomolybdic acid-based polyionic liquid and preparation method and application thereof
By using aqueous porous phosphomolybdate-based polyionic liquid catalyst in oxidative desulfurization technology, the problems of poor removal effect of aromatic sulfides and difficulty in recovery of catalysts in traditional technology are solved, and efficient oxidative desulfurization effect and good catalyst circulation are achieved. stability.
Patent Information
- Application Number
- CN202211233700.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-10
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-10-10
AI Technical Summary
Traditional hydrodesulfurization technology has poor effect and high cost in removing aromatic sulfides. The difficulty in recycling and separation of catalysts in existing oxidative desulfurization technologies limits the development of ultra-low sulfur fuel oil.
The aqueous porous phosphomolybdate-based polyionic liquid (PDIM-PMo-W) is used as a catalyst to introduce water into the hybrid of heteropolyacid polymerized ionic liquid, affecting the oxidation and desulfurization system and improving the solubility and catalytic activity of the catalyst.
The oxidation and desulfurization effect is significantly improved, the catalyst has good recycling ability, and it can not significantly change the catalytic activity in at least five cycles, and the water absorption behavior is reversible, maintaining catalytic activity.
Smart Images

Figure CN115612003B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oxidative desulfurization, and in particular relates to a water-containing porous phosphomolybdic acid-based polyionic liquid and a preparation method and application thereof. Background Art
[0002] Organic sulfur compounds in fuel oil are converted into SOx and discharged into the air during combustion, which causes serious environmental pollution and human health problems. In recent years, many countries and regions have issued strict regulations to limit the sulfur content in fuel oil to a low level (<10 ppm). In order to obtain ultra-low sulfur fuel oil, it is imperative to develop efficient deep desulfurization technology. At present, although traditional hydrodesulfurization (HDS) technology is widely used in industrial production for efficient removal of aliphatic sulfides, its development is limited by its high cost, harsh reaction conditions and poor removal effect of aromatic sulfides. Therefore, it is of great significance to develop efficient and mild desulfurization technologies such as oxidative desulfurization (ODS), adsorption desulfurization, extractive desulfurization and biological desulfurization. Among them, ODS, as a desulfurization technology with high selectivity and low energy consumption for removing aromatic sulfides, is considered to be one of the most suitable methods for producing ultra-low sulfur fuel oil.
[0003] Polyoxometalates (POMs) are a class of structurally precise anionic clusters composed of transition metal oxides. They have been widely used in the field of oxidation catalysis due to their high thermal stability, reversible multi-electron redox ability, and strong persistence to oxidants. In particular, Keggin-type POMs can effectively activate oxidants to obtain highly active peroxides and show good removal effects on thiophene sulfides. However, due to the good solubility of POM in polar solvents, it is usually used as a homogeneous catalyst, which makes the recovery and separation of the catalyst difficult. To solve this problem, the introduction of organic counterions is one of the effective methods to regulate the solubility and surface microenvironment of POM.
[0004] Polyionic liquids (PILs) are multifunctional polyelectrolytes polymerized from ionic liquid (IL) monomers, which have many advantages such as designable structure, good processing performance, high stability, and adjustable solubility. Therefore, PILs are selected as counterions to prepare heteropolyacid-based polymerized ionic liquid hybrids for application in the field of oxidative desulfurization. Long carbon chain organic cations have good affinity with the oil phase and are therefore usually selected as polyionic liquid monomers. This type of catalyst has super lipophilicity and contains a hydrophilic active component POM, which is beneficial to interphase mass transfer and improves catalytic activity. It is worth noting that the pore structure can be formed by ion self-assembly using PIL and POM with highly delocalized negative charges, and the pore structure can accommodate guest water molecules. Summary of the invention
[0005] The present invention believes that the presence of water may be more conducive to the diffusion of H2O2 in the ODS catalyst channel. Therefore, the present invention proposes a new design strategy to introduce water into the heteropolyacid polymer ionic liquid hybrid, thereby affecting the ODS system. 12 O 40 A novel aqueous porous phosphomolybdic acid-based polyionic liquid (PDIM-PMo-W) was prepared using poly(HPMo) and poly(3-dodecyl-1-vinylimidazolium) bromide (PDIMBr) as raw materials and applied to oxidative desulfurization (ODS).
[0006] The present invention first provides a water-containing porous phosphomolybdic acid-based polyionic liquid PDIM-PMo-W, with H3PMo 12 O 40 It was prepared using poly (HPMo) and poly [3-dodecyl-1-vinylimidazolium] bromide (PDIMBr) as raw materials.
[0007] Among them, the water content of the aqueous porous phosphomolybdic acid-based polyionic liquid is 40% to 70%, and the oxidative desulfurization effect increases with the increase of the water content. That is, when the water content of the aqueous porous phosphomolybdic acid-based polyionic liquid is 70%, the oxidative desulfurization effect is the best.
[0008] The present invention also provides a method for preparing the above-mentioned aqueous porous phosphomolybdic acid-based polyionic liquid, comprising the following steps:
[0009] Step 1: Preparation of PDIMBr. Specifically, DIMBr and 2,2-azobisisobutyronitrile (AIBN) were dissolved in anhydrous ethanol, and the mixture was stirred at 70°C under a nitrogen atmosphere for 24 hours. The product was precipitated in deionized water and washed with deionized water, and finally vacuum dried at 60°C for 24 hours to obtain PDIMBr; wherein the concentrations of DIMBr and AIBN in anhydrous ethanol were 0.5833 mol / L and 0.0204 mol / L, respectively.
[0010] Step 2: H3PMo 12 O 40The aqueous porous phosphomolybdic acid-based polyionic liquid PDIM-PMo-W was prepared using poly(HPMo) and poly[3-dodecyl-1-vinylimidazole] bromide (PDIMBr) as raw materials. Specifically, the ethanol solution of PDIMBr was slowly dripped into the aqueous solution of HPMo, stirred at room temperature for 2 hours, and then heated at 100°C for 21 hours. The solid product was separated by centrifugation and washed with ethanol and deionized water in turn. Then it was vacuum dried at 50°C for no more than 24 hours to obtain the target product. The concentration of the ethanol solution of PDIMBr was 0.0251 mol / L, the concentration of the aqueous solution of HPMo was 0.0233 mol / L, and the molar ratio of PDIMBr to HPMo was 4.3.
[0011] The present invention also provides the use of the above-mentioned aqueous porous phosphomolybdic acid-based polyionic liquid as a catalyst in oxidative desulfurization, specifically catalyzing DBT oxidative desulfurization.
[0012] The beneficial effects of the present invention are:
[0013] PDIM-PMo-W of the present invention 70% The turnover frequency (TOF) value for the removal of dibenzothiophene (DBT) can reach 41.15 h at 50 °C. ‒1 , which are 35.47 and 9.92 times of HPMo and PDIM-PMo, respectively. In addition, the catalyst can be recycled at least five times without significantly changing its catalytic activity.
[0014] The present invention finds that the water absorption behavior of the catalyst is reversible, and the dry catalyst can still exhibit excellent catalytic activity after being immersed in water. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 a is the thermogravimetric analysis diagram of the water content of the catalyst at different drying times; Figure 1 b is the conversion rate of DBT by catalysts with different water contents.
[0016] Figure 2 (a) Effect of different reaction temperatures on DBT conversion; (b) Pseudo-first-order kinetics of DBT conversion at different temperatures; (c) Effect of different catalyst dosages on DBT conversion; (d) Effect of different H2O2 / S (molar ratio) on DBT conversion. Reaction conditions: Model oil for all reactions (5 mL, sulfur content: 500 ppm). (a) Catalyst dosage = 20 mg, H2O2 / S = 4 (23 µL); (b) Catalyst dosage = 20 mg, H2O2 / S = 4; (c) T = 50 °C, H2O2 / S = 4; (d) Catalyst dosage = 20 mg, T = 50 °C.
[0017] Figure 3a is the cyclic stability analysis diagram of catalyst PDIM-PMo-W70%; Figure 3 b is the infrared spectra of fresh PDIM-PMo and recycled PDIM-PMo (the recycled PDIM-PMo was washed with ethanol). Reaction conditions: catalyst dosage = 20 mg, H2O2 / S = 4, T = 50℃.
[0018] Figure 4 The cyclic stability analysis diagram of the dehydration catalyst soaked in water. Reaction conditions: catalyst dosage = 20 mg, H2O2 / S = 4, T = 50 °C. DETAILED DESCRIPTION
[0019] The present invention is described in more detail below through specific implementation modes to facilitate understanding of the technical solution of the present invention, but is not intended to limit the protection scope of the present invention.
[0020] Example 1
[0021] 1. Preparation of PDIMBr
[0022] DIMBr (12 g, 35 mmol) and AIBN (3.5% of the monomer molar weight) were dissolved in anhydrous ethanol (60 mL). The mixture was then stirred at 70 °C under a nitrogen atmosphere for 24 hours. After the reaction was completed, the mixture was added dropwise to 500 mL of deionized water to obtain the precipitate PDIMBr, which was then washed three times with deionized water and finally dried under vacuum at 60 °C for 24 hours to obtain the product PDIMBr.
[0023] Preparation of PDIM-PMo with different water contents
[0024] The PDIM-PMo hybrid is prepared by an anion exchange reaction, which specifically includes the following:
[0025] PDIMBr (1.505 mmol calculated as monomer repeating unit) and HPMo (0.35 mmol) were dissolved in 60 mL of ethanol and 15 mL of water, respectively, to form solution A and solution B. Then, solution A was slowly dripped into solution B at room temperature and stirred at room temperature for 2 hours. The mixture was transferred to a 100 mL polytetrafluoroethylene-lined reactor and heated at 100 °C for 21 h. The solid product was separated by centrifugation and washed with ethanol and deionized water in sequence. Products with different water contents were obtained by vacuum drying at 50 °C for 8 hours, 12 hours, 16 hours and 24 hours, respectively, and were denoted as PDIM-PMo-W. 70% 、PDIM-PMo-W 60% 、PDIM-PMo-W 40%and PDIM-PMo (i.e., anhydrous product). This example measures the water content of the catalyst at different drying times by thermogravimetric analysis, such as Figure 1 The water content refers to the mass ratio of water in the whole catalyst.
[0026] Effect of catalysts with different water contents on oxidative desulfurization
[0027] DBT was dissolved in n-octane and n-dodecane was used as the internal standard to obtain a model oil with a sulfur concentration of 500 ppm. In a typical reaction, 20 mg of catalyst and 5 mL of model oil were added to an 8 mL reaction vial, and then H2O2 (30%, 23 µL) was added and the reaction was started under stirring (555 r / min). Samples were taken at intervals and analyzed for sulfur content by gas chromatography.
[0028] The results show that the oxidative desulfurization effect gradually improves with the increase of water content in the catalyst. Figure 1 b. Under the same reaction conditions, the conversion rate of DBT with a catalyst containing 70% water can reach 100% in 40 minutes, while that of a completely dry catalyst is only 33.6%. The catalytic performance of the water-containing catalyst is significantly better than that of the completely dry catalyst. In addition, the conversion rates of DBT using PDIMBr and pure HPMo as catalysts in the ODS system are 15.4% and 15.2%, respectively.
[0029] It is worth noting that the PDIM-PMo-W 70% The measured element mass ratios are C: 30.46%; N: 4.10%; H: 4.545%; the mass ratio of PDIM is 39.095%, and PMo is deduced. 12 O 40 3- The mass ratio is 60.905%, of which PMo 12 O 40 3- The relative molecular mass of PDIM-PMo-W is 1822.49. According to the formula: TOF = moles of converted DBT / (moles of isopolyanions × reaction time (h)), at 50°C, 70% The turnover frequency (TOF) value can reach 41.14 h ‒1 , which are 35.47 and 9.92 times of HPMo and PDIM-PMo, respectively.
[0030] Effects of different reaction temperatures, catalyst dosages, and oxygen-sulfur ratios on DBT conversion
[0031] 20 mg of catalyst and 5 mL of model oil were added to an 8 mL reaction vial, and then H2O2 was added. The reaction was started under stirring (555 r / min), and different reaction temperatures were set at 30°C, 40°C, 50°C, and 60°C, with H2O2 / S (molar ratio) of 4. Samples were taken at regular intervals and the sulfur content was analyzed by gas chromatography. Figure 2 a shows the effect of different reaction temperatures on DBT conversion. When the temperature increases from 30°C to 50°C, the DBT conversion rate increases significantly from 80.2% to 100% within 40 min. The desulfurization rate does not increase significantly when the temperature is further increased to 60°C. This may be due to the violent decomposition of H2O2 at high temperatures. Therefore, 50°C is selected as the most suitable reaction temperature.
[0032] In order to better explain the relationship between temperature and DBT conversion, the kinetics of oxidative desulfurization were studied. t The curve of the change of / C0) with time conforms to pseudo-first-order kinetics, and low reaction temperature corresponds to low reaction rate ( Figure 2 b). According to the Arrhenius equation, the oxidation reaction of DBT has a low apparent activation energy (34.6±2.6 kJ / mol), which indicates that the catalyst significantly increases the reaction rate of DBT oxidation reaction.
[0033] 5 mg, 10 mg, 20 mg and 40 mg of catalyst and 5 mL of model oil were added to an 8 mL reaction vial, and then H2O2 was added. The reaction was started under stirring (555 r / min), and the reaction temperature was set to 50 °C and the H2O2 / S (molar ratio) was 4. Samples were taken at regular intervals and the sulfur content was analyzed by gas chromatography. Figure 2 As shown in Figure c, when the catalyst dosage increased from 5 mg to 30 mg, the DBT conversion rate increased significantly from 66.2% to 100% after 40 min of reaction, indicating that ODS is significantly affected by the catalyst dosage. This is because increasing the amount of catalyst can directly increase the number of active centers. When the catalyst dosage is 20 and 40 mg, DBT can be fully converted at the same time. Therefore, from an economic point of view, 20 mg is selected as the best dosage.
[0034] This example also studies the effect of H2O2 / S on DBT conversion efficiency. 20 mg of catalyst and 5 mL of model oil were added to an 8 mL reaction vial, and then H2O2 was added. The reaction was started under stirring (555 r / min), and the reaction temperature was set to 50°C. The H2O2 / S (molar ratio) was 2, 4, 6, and 8. Samples were taken at regular intervals and analyzed for sulfur content by gas chromatography. Figure 2As shown in Figure d, when H2O2 / S (molar ratio) is 2, the reaction rate is relatively low, and the DBT conversion rate is only 76% after 120 min. However, when H2O2 / S increases to 4, DBT can be completely removed within 40 min. When H2O2 / S increases further, the conversion efficiency of DBT is no longer sensitive to H2O2 / S. Therefore, in terms of economy and efficiency, H2O2 / S is selected as 4.
[0035] In general, the optimal reaction conditions are 5 ml of model oil, 500 ppm sulfur content, 20 mg of catalyst, H2O2 / S = 4 (23 µL), and a reaction temperature of 50 °C. 70% DBT can be completely removed within 40 minutes.
[0036] Catalyst PDIM-PMo-W 70% Cyclic stability analysis
[0037] Under the optimal reaction conditions, after each reaction, the liquid was carefully removed by centrifugation, and then H2O2 and fresh model oil were added for a new cycle test. After five cycles, the conversion rate of DBT could still reach 99% ( Figure 3 a), indicating that the catalyst has good cycling performance.
[0038] In addition, the recovered catalyst was washed with ethanol several times to remove the oxidation products, and then the FT-IR spectra of the recovered catalyst and the fresh catalyst were compared. a 、Mo-O d 、Mo-O b -Mo and Mo-O c The characteristic peaks of -Mo are located at 1060, 960, 882 and 810 cm ‒1 The peaks can be clearly distinguished from each other, and no additional peaks appear in the recovered catalyst ( Figure 3 b), indicating that the catalyst has good stability in the ODS system.
[0039] In addition, the completely dried catalyst PDIM-PMo was added to 5 ml of water and then ultrasonicated for 5 minutes to quickly immerse the catalyst in water. Then, after soaking for 12 hours, a water-containing catalyst was obtained, indicating that the water absorption behavior of the catalyst is reversible. And the water-containing catalyst prepared in this way can still achieve 100% DBT removal efficiency after five cycles. Figure 4 shown.
[0040] The embodiments described above are only preferred embodiments of the present invention and are not intended to limit the scope of implementation of the present invention. Therefore, any equivalent changes or modifications made according to the structures, features and principles described in the patent scope of the present invention should be included in the scope of the patent application of the present invention.
Claims
1. Aqueous porous phosphomolybdic acid-based polyionic liquid, characterized in that: The aqueous porous phosphomolybdic acid-based polyionic liquid is H3PMo 12 O 40 The invention is prepared by using poly[3-dodecyl-1-vinyl imidazole] bromide as raw materials; the water content of the water-containing porous phosphomolybdic acid-based polyionic liquid is 40% to 70%.
2. The method for preparing the aqueous porous phosphomolybdic acid-based polyionic liquid according to claim 1, characterized in that: The following steps are involved: Step 1: Preparation of PDIMBr; Step 2: H3PMo 12 O 40 and poly[3-dodecyl-1-vinylimidazolium] bromide as raw materials to prepare the aqueous porous phosphomolybdic acid-based polyionic liquid PDIM-PMo-W.
3. The method according to claim 2, characterized in that Step 1 is specifically as follows: DIMBr and AIBN are dissolved in anhydrous ethanol, and then the mixture is stirred and reacted at 70° C. in a nitrogen atmosphere, and then precipitated and washed in deionized water, and finally vacuum dried at a temperature of 60° C. to obtain PDIMBr.
4. The method according to claim 3, characterized in that The concentrations of DIMBr and AIBN in anhydrous ethanol are 0.5833 mol / L and 0.0204 mol / L, respectively.
5. The method according to claim 2, characterized in that: Step 2 is specifically as follows: slowly dripping the ethanol solution of PDIMBr into the aqueous solution of HPMo, stirring at room temperature, and heating the reaction at 100°C; then centrifuging and separating the solid product, washing it with ethanol and deionized water in turn; and then vacuum drying it at 50°C for no more than 24 hours to obtain the target product.
6. The method according to claim 5, characterized in that The concentration of the ethanol solution of PDIMBr is 0.0251 mol / L, the concentration of the aqueous solution of HPMo is 0.0233 mol / L, and the molar ratio of PDIMBr to HPMo is 4.
3.
7. Use of the aqueous porous phosphomolybdic acid-based polyionic liquid according to claim 1 as a catalyst in oxidative desulfurization.
8. The use according to claim 7, characterized in that: Aqueous porous phosphomolybdic acid-based polyionic liquid was used as a catalyst to catalyze the oxidative desulfurization of DBT.
Citation Information
Patent Citations
Supported heteropolyacid catalyst, and preparation method and application thereof
CN106732779A
